Chlorophenols in leachates originating from different landfills and aerobic composting plants - Ozkaya, B (ELSEVIER, 2005)
Both type and concentration of organic contaminants in landfill leachates show great variation depending on many factors, such as type of wastes, rate of water application, moisture content, landfill design and operation age. In this paper, highly toxic chlorophenol derivatives, poorly biodegradable, carcinogenic existence and recalcitrant properties are determined by solid phase microextraction (SPME)-GC/FID in different leachates from landfill and composting plant in Istanbul. Leachates originated from acidogenic, methanogenic phases of Odayeri sanitary landfill (OSL) and from an aerobic composting plant are considered for different chlorophenol types. It is observed that acidogenic leachate from Odayeri landfill includes 2,4-dichlorophenol, 2,6-dichlorophenol, 2,3,4-trichlorophenol, 2,3,4,5-tetrachlorophenol and 2,3,4,6-tetrachlorophenol at concentration ranges, 15- 130, 18-65, 8-40, 5-20 and 10-25 mu g/l, respectively. Whereas, only 2,4-dichlorophenol at a concentration range 8-40 mu g/l is determined in the methanogenic leachate of the landfill, which can be considered as an indication of reductive dechlorination. There is no chlorophenol derivative in aerobic composting leachate. It is determined that acidogenic leachate from Odayeri landfill includes more species of chlorinated phenols at higher concentration. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chlorophenols; composting; landfill; leachate; SOLID-PHASE MICROEXTRACTION; CHROMATOGRAPHY MASS-SPECTROMETRY; ACCLIMATED ACTIVATED-SLUDGE; ORGANIC-COMPOUNDS; BIODEGRADATION KINETICS; VOC TRANSPORT; WASTE-WATER; OPTIMIZATION; CONTAMINANTS; POLLUTANTS; Engineering; Environmental Sciences & Ecology